Institutional, policy and actor interactions in disaster risk management: insights from Kenya - Mohamed, Tahira Shariff (International Livestock Research Institute, 2025)
Presented at IGAD Centre for Pastoral Areas and Livestock Development (ICPALD), the Jameel Observatory for Food Security Early Action and the Supporting Pastoralism and Agriculture in Recurrent and Protracted Crises (SPARC) Programme 'Building the Resilience and Prosperity of Pastoralists and Dryland Communities' research and policy dialogue in Nairobi on 1 and 2 October 2025